Humanity over economy: Biopolitical responses to the COVID-19 pandemic in Ghana - James McKeown (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This study posits that pandemics should be regarded as complex, open-ended phenomena that cannot be reduced to biology and epidemiology. The research assesses Ghana's effectiveness in governing the COVID-19 pandemic contrary to apocalyptic predictions. This paper critiques Ghana's responses to the COVID-19 pandemic through the lens of Foucault's biopolitics. The main result of this study showed that Ghana survived the pandemic because of effective policies, not providence. The study also found that the 'Ghana Beyond Aid' self-reliance agenda was given further impetus. The study concludes that the moderately intrusive biopolitical responses to COVID-19 did not deteriorate democratic norms in Ghana.
Keywords: I15; H12; J88; 330; COVID-19; humanity; biopolitics; government effectiveness; biosurveillance; paradoxes; Ghana